(untitled) (Chittagong University Journal of Biological Sciences, 2024)
In vitro root induction was observed in cucumber as influenced by varieties and IBA concentrations. Four cucumber varieties viz. Shila, Green Field, Shital and Shahi-50 and three IBA concentrations viz. 0.0 (Control), 1.0, and 2.0 mg l-1 were used in this investigation. The Shital variety with in maximum number and the highest percentage of shoot produced roots. No root induction was observed when medium was auxin free. Higher concentration of IBA resulted in higher number (3.94) and percentage (98.65 %) of root. Half strength MS medium when fortified with 2.0 mg l-1 IBA took minimum time (6.88 days). Combined effect of varieties and IBA concentrations were found significant in all the parameters studied. The highest number (19.54) of roots were obtained from variety Shital when they were interacted with higher IBA concentration (2.0 mg l-1) followed by the interaction of same variety with lower concentration (19.18). The highest root length (8.80 cm) was found in the interaction of Shila x 2.0 mg l-1 IBA and the lowest root length (6.31 cm) was found in the interaction of Shahi-50 x 1.0 mg l-1 IBA. The Chittagong Univ. J. B. Sci.,Vol. 7(1 &2):01-10, 2012